Rethinking Paulo Freire: Esensi Tentang Pendidikan Yang Membebaskan Dan Relevansinya Pada Masa Kini - prastawa, Singgih; Tonny Rey, Kevin (YPI Ulul Albab, 2025)
Education is the need of every individual who needs knowledge. Education has a strong foundation for thinking, namely to present human values. Education that produces problems is education that does not have a strong construction basis. Education is actually a deliberate and programmed effort with the aim of a change for the learner and others. Education should be implemented with respect and appreciation of human values. Not education that makes learners like programmed robots by eliminating their self-awareness so that it is difficult to bring about transformation. Freire offers an alternative to education that is based on the paradigm of intellectual and emotional freedom awareness that is ultimately able to produce social transformation. The education initiated is also based on a rational critical dialogical framework so that the creativity of the subject emerges and is able to communicate human values. Freire's education can still be accepted in the present time where there is still a concept of education that eliminates the awareness of freedom of subjects to become objects that suffer or are oppressed.Education